(untitled) (Filološke pripombe, 2019)
The article «Requium» by Akhmatova: geography and the model of space deals with the formation of the universal model of the literary space within the creative work of A. Akmatova. The process of transformation of ordinary geographical concepts into «eternal images» of culture is under specific consideration.